Diversity and distribution of epiphytic lichens and bryophytes on aspen (Populus tremula) in the middle boreal forests of Republic of Karelia (Russia) - Tarasova, Viktoria N.; Obabko, Roman P.; Himelbrant, Dmitry E.; Boychuk, Margarita A.; Stepanchikova, Irina S.; Borovichev, Eugene A. (Folia Cryptogamica Estonica, 2017)
The distribution of epiphytic bryophyte and lichen species growing on aspen in the middle boreal forests was studied in southern Karelia (Russia). These forests varied in time-since-disturbance from 80 to 450 years. Two hundred twenty two species of epiphytes, including 178 lichens, 32 mosses and 12 liverworts, were recorded on 192 aspen trees in forests over 24 ha, in the Karelian part of the Vodlozero National Park, Kivach Strict Nature Reserve, Kizhi Sanctuary and Petrozavodsk City. Arthonia biatoricola, A. excipienda and Biatoridium monasteriense were collected in Karelia for the first time. Eighteen rare species (lichens Anaptychia ciliaris, Arthonia vinosa, Bryoria nadvornikiana, Chaenotheca gracilenta, C. stemonea, Lecidea albofuscescens, Lobaria pulmonaria, Melanelixia subaurifera, Nephroma bellum, N. laevigatum, Phaeocalicium populneum, Ramalina thrausta, Rostania occultata, Scytinium subtile, Usnea barbata, mosses Neckera pennata, Plagiomnium drummondii and liverwort Lejeunea cavifolia) listed in the Red Data Book of Republic of Karelia (2007) were found. Relationships between epiphytic lichen and bryophyte species richness and certain environmental variables (at different trunk heights above ground and time-since-disturbance) were evaluated. Lichens and mosses on aspen trunks often occupy different ecological niches. Cover and diversity of bryophytes was high on trunk bases, while the number of lichen species and their cover were higher at a height of 1.3 m above ground level. The total number of lichen species on aspen increased on average from 40 to 60 species per ha with increasing time-since-disturbance from 100 to 450 years. A stabilization in lichen species number was observed at about 200 years since disturbance. No significant correlation was determined between bryophyte diversity on aspens and the time-since-disturbance.